An ethnobotanical perspective on traditional fermented plant foods and beverages in Eastern Europe. (21st July 2015) - Sõukand, Renata; Pieroni, Andrea; Biró, Marianna; Dénes, Andrea; Dogan, Yunus; Hajdari, Avni; Kalle, Raivo; Reade, Benedict; Mustafa, Behxhet; Nedelcheva, Anely; Quave, Cassandra L.; Łuczaj, Łukasz
Abstract: Ethnopharmacological relevance: Fermented food and beverages represent an important part of the worldwide foodscape, medicinal food domain and domestic strategies of health care, yet relevant traditional knowledge in Europe is poorly documented. Methods: Review of primary ethnographic literature, archival sources and a few ad-hoc ethnobotanical field studies in seven selected Eastern European countries (Albania, Belarus, Bulgaria, Estonia, Hungary, Kosovo, and Poland) were conducted. Results: Current or recently abandoned uses of 116 botanical taxa, belonging to 37 families in fermented food or medicinal food products were recorded. These findings demonstrate a rich bio-cultural diversity of use, and also a clear prevalence of the use of fruits of the tannin- and phenolic-rich Rosaceae species in alcoholic, lactic- and acetic acid fermented preparations. In the considered countries, fermentation still plays (or has played until recent years) a crucial role in folk cuisines and this heritage requires urgent and in-depth evaluation. Discussion: Future studies should be aimed at further documenting and also bio-evaluating the ingredients and processes involved in the preparation of homemade fermented products, as this can be used to support local, community-based development efforts to foster food security, food sovereignty, and small-scale local food-based economies. Graphical abstract: